VISUALISASI KALIGRAFI ISLAM PADA MEDIA SENI RUPA DI INDONESIA (ANALISIS ETIKA, ESTETIKA, DAN NILAI-NILAI) - Muhapril Musri (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
The presence of art as an expression can be assumed as a characteristic of the soul's life which is overflowing and arid from values. That is why, the artists try to find the values of life that are full of values, by pouring their ideas and ideas in the form of works of art. The method used in this research is descriptive qualitative with literature and field studies. Two Islamic calligraphers were involved as resource persons. As a result, the current strong influence of modern art has caused Islamic calligraphy to be affected. This can be seen from the emergence of various tendencies of Muslim artists in processing Islamic calligraphy into various media. Previously, calligraphy had not been realized as a form of personal expression, but now this awareness has emerged in the form of the phenomenon of calligraphy painting. Calligraphy painting as a reflection of the modern spirit of Muslim artists has provided fresh air for the development of Islamic art and culture in Indonesia. Uniquely, in Indonesia, calligraphy painting was born in the hands of conventional painters who had not previously been in the world of Islamic calligraphy directly.